Towards a better understanding of time-lags in karst aquifers by combining hydrological analysis tools and dye tracer tests. Application to a binary karst aquifer in southern Spain - Martín-Rodríguez, José Francisco; Mudarra-Martínez, Matías; De la Torre Martínez, Beatriz; Andreo-Navarro, Bartolomé (Elsevier, 2023)
The assessment of the response time of a karst aquifer is an important step towards the development of conceptual models from which tools for water resources planning and management could be applied. The aim of this work is to evaluate the applicability of the joint use of statistical time-lag evaluation and dye tracer tests techniques with a double objective: 1) the development of conceptual models on the hydrogeological functioning that include the duality in the aquifer recharge processes, as well as the particularities of the preferential drainage flowpaths respect to the global response of the aquifers; 2) to establish a reference frame to foresee with enough time in anticipation the potential affections derived from the concentrated recharge to the springs, required in the creation of water quality monitoring networks and early warning systems to water pollution. In the Ubrique karst aquifer (southern Spain), the empirical relationships between the intensity (I) of rainfall events (recharge) and the time-lag (T) observed in the springs that draining the aquifer have been quantified. The establishment of the curve (I-T) constitutes a reliable tool for the prediction of potential affections to the springs (intended for urban supply) derived from recharge events. On the other hand, the comparison of the values drawn in the I-T curve, characteristic of each spring, with those derived from three tracer tests, has allowed further advances in the understanding of the aquifer functioning and the influence of concentrated recharge on the global system behavior to be achieved.
Keywords: Acuíferos - España; Hidrogeología; Carbonate (karst) aquifer; Time-lag Recharge; Dye tracer test; Cross correlation function; Southern Spain